Generation X and Y: Impact of Work Attitudes and Work Values on Employee Performance - Usmani, Sania; Asif, Muhammad Haris; Mahmood, Muhammad Zaid; Khan, Muhammad Yousuf; Burhan, Mir (Journal of Management and Research, 2019)
Sustainable competitive advantage lies in the intellectual capital of firms, where it has become important to retain employees and train them for future leadership. Hence, firms must recognize the importance of the work values and attitudes of the employed Generation. Understanding Generational diversity and using the right strategy is crucial for the firm’s success. Theorization of Generational differences have been applied in Western Cultures more often than Eastern Cultures, hence this research expanded the concept of Generational diversity to the banking workforce of Karachi, Pakistan. The relationship between Generation X and Y work values and attitudes on employee performance was examined. Three hundred people from Generation X and Y were taken as a sample from the Commercial Banks in Karachi and responses on different work attitudes and values were taken. It was found that values and attitudes have a significant relationship with employee performance for both Generation X and Y. However, cognitive and social values are important for Generation X while cognitive, instrumental and prestige values are important for Generation Y employees. The study theoretically contributes to work values and attitudes perspective, generational theory and performance perspective and offers implications for creating a suitable combination of tasks and rewards with respect to individual needs.